Effective Load Management System for Sudden Shutdown Avoidance of Stand Alone Photovoltaic Operation - Nuratiqah, Mohd Isa; Amirah Nurhafizah, Abu Bakar; Nurul Husna, Mohd Sarif; Mohamad Shaiful, Abdul Karim; Ahmad Syahiman, Mohd Shah (IOP Publishing, 2021)
Stand-alone system is the system that operates independently of the electrical grid. Conventionally, the energies absorbed through photovoltaic modules are stored in batteries to reserve for night-time use. Moreover, the function of batteries in stand-alone system is to stabilize the output supplied for the load particularly during the fluctuating circumstance. Sudden shutdown of dedicated photovoltaic system during this period may occur when the storage of batteries approaches empty level which may significantly degrade the lifespan and performance of the batteries. In this study, a sequential load switching system is introduced in order to overcome the sudden shutdown of storage battery-based photovoltaic system. The developed system is mainly equipped with Arduino, MOSFETs and DC bulbs as microcontroller, high-speed switching and load, respectively. As a result, the proposed sequential load switching method is highly effective since it has successfully extended the standby time period up to approximately 27 times longer, before the system shutdowns at the cut-off voltage.